Building Mental Toughness in Indonesian Islamic Boarding Schools: Socio-Emotional Adaptation and Education in the Global South - Azam Syukur Rahmatullah; Dewi Sekar Kencono; Eko Harianto; Muhammad Hisyam Syafii (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This study examined a structural model in which self-efficacy, emotion regulation, adaptive coping, and socio-emotional factors (social support, social adjustment, and religious coping) predict mental toughness among students in Indonesian Islamic boarding schools (pesantren). A total students from 12 pesantren in Central Java and Yogyakarta participated; after data screening, 654 respondents (95.2% valid response rate) were retained for analysis. Mental toughness, emotion regulation, self-efficacy, and adaptive coping were measured using the Mental Toughness Questionnaire-48 (MTQ48), Emotion Regulation Questionnaire (ERQ), General Self-Efficacy Scale (GSE), and Brief COPE, while socio-emotional factors were measured using the Perceived Social Support Scale (PSSS), Social Adjustment Scale-Self Report (SAS-SR), and Religious Coping Scale (RCOPE), all adapted for the pesantren context through translation, back-translation, and pilot testing. Data were analyzed using Structural Equation Modeling (SEM) in AMOS version 28.0. The hypothesized model showed excellent fit to the data, χ²(247) = 389.74, p < .001, χ²/df = 1.58, CFI = .97, TLI = .96, RMSEA = .031 (90% CI [.025, .037]), SRMR = .041. Self-efficacy showed the strongest direct effect on mental toughness (β = .35, p < .001), followed by emotion regulation (β = .28, p < .001) and adaptive coping (β = .18, p < .001). Among socio-emotional factors, social adjustment had the strongest effect (β = .16, p < .001), and its indirect pathway through self-efficacy was the strongest mediating mechanism identified (point estimate = .109, 95% CI [.068, .155]). These findings indicate that psychological resources, rather than socio-emotional resources alone, are the primary proximal drivers of mental toughness in the pesantren context, with socio-emotional support operating largely through its influence on self-efficacy. Practical implications point toward psychopedagogical programs that prioritize self-efficacy and emotion-regulation training, supported by structured mentoring and religious coping resources.